2019
DOI: 10.3390/geosciences9090377
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Influence of Polypropylene Fiber on the Swelling Pressure Expansion Attributes of Silica Fume Stabilized Clayey Soil

Abstract: Expansive soil shows dual swell-shrink which is not suitable for construction. Several mitigating techniques exist to counteract the problem promulgated by expansive clayey soils. This paper explored the potential mecho-chemical reinforcement of expansive clayey soil to mitigate the effect of upward swelling pressure and heave. The polypropylene fiber is randomly distributed in the soil for mechanical stabilization, and the industrial residual silica fume is used as a chemical stabilizer. The experimental anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…The four types of samples have been prepared to investigate the effect of curing methods on freezing-thawing cycle of PP fiber-reinforced, and silica fume stabilized expansive soil: (1) an untreated sample; (2) an SF stabilized sample; (3) a PP Fiber-reinforced samples, and (4) a PP fiber-reinforced and SF stabilized sample. The expansive soil has been reinforced with 0.25%, 0.50%, and 1.00% PP fiber and stabilized with 2%, 4%, 6%, and 8% SF as reported by Tiwari and Satyam (2019) 63 . The expansive soil samples were air-dried until a stable state was reached.…”
Section: Sample Preparationmentioning
confidence: 86%
See 3 more Smart Citations
“…The four types of samples have been prepared to investigate the effect of curing methods on freezing-thawing cycle of PP fiber-reinforced, and silica fume stabilized expansive soil: (1) an untreated sample; (2) an SF stabilized sample; (3) a PP Fiber-reinforced samples, and (4) a PP fiber-reinforced and SF stabilized sample. The expansive soil has been reinforced with 0.25%, 0.50%, and 1.00% PP fiber and stabilized with 2%, 4%, 6%, and 8% SF as reported by Tiwari and Satyam (2019) 63 . The expansive soil samples were air-dried until a stable state was reached.…”
Section: Sample Preparationmentioning
confidence: 86%
“…The chemical stabilization is a substantiate quick-fix method to improve the shear strength and also reduces the swelling shrinkage nature of expansive soil [24][25][26][27] . Nonetheless, there are substantial problems for the long-term viability of these approaches, depending on soil clay mineralogy, ecological variations in clay 19 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, conventional methods are replaced by advanced emerging techniques for improving the properties of granular soils. The use of supplementary cementitious materials, nanomaterials, synthetic fibers, industrial waste products, and biopolymers are found effective for strength enhancement (Huang and Wang 2016; Tiwari and Satyam, 2019, 2020; Tiwari et al., 2020a, 2020b, 2020c). However, the high cost of treatment and field application of these methods are the major challenges.…”
Section: Introductionmentioning
confidence: 99%